Pola Interaksi Siswa-Siswi Kristen dan Muslim dalam Membangun Toleransi Beragama - Nur Ashrofiah, Putri; Hafil, Ach. Shodiqil (Journal of Islamic and Social Studies, 2023)
This research is to describe the form of their social interaction in building religious tolerance. Data collection was carried out directly by conducting field research at the research location. To achieve the objectives of this study, qualitative methods were used. The place of this research is at SMAN 8 Kediri. The object of this research is the students of SMAN 8 Kediri. Data collection techniques through observation, interviews and documentation. This study involved all 10th graders of SMAN 8 Kediri. From the results of the study it can be concluded that religion is a belief held by humans. With the existence of religion as the unification of individuals in a community group. However, religious differences then do not become a conflict or difference between individuals with other individuals. How to maintain that there are no differences between individuals, namely by tolerant and interacting. This interaction is very important for all social beings. With the interaction of individuals with individuals can achieve a certain goal. Differences in beliefs will not be a barrier in establishing a relationship and do not make a difference in individuals, precisely with this difference it is very important to build a sense of Bhinneka Tunggal Ika. This study uses the theory of symbolic interactionism where this theory is very suitable to find out the ways or patterns of interaction between Christian minority students and the Muslim majority. This theory comes from one of the sociology figures, namely George Herbert Mead. This theory is a theory used by researchers can see from various points of view and that can be through body gestures or even symbols of actions taken by the person being studied..